Effect of Mill Type and Particle Size Variation on Growth Performance and Carcass Characteristics of Finishing Pigs - M. B. Braun; H. K. Wecker; A. Yoder; J. C. Woodworth; C. R. Stark; C. B. Paulk (Kansas Agricultural Experiment Station Research Reports, 2018)
The objective of this experiment was to determine the effects of mill type used to grind corn and its particle size variation on diet flowability and subsequent finishing pig growth performance and carcass characteristics. A total of 200 pigs (DNA Line 241 × 600; initially 121.9 lb) were used in a 75-d growth trial. Pigs were randomly assigned to pens with either 5 barrows or 5 gilts per pen. Pens were then randomly allotted to 1 of 4 treatments balanced by weight and gender with 10 pens per treatment. Treatments were arranged as a 2 × 2 factorial with 2 mill types (3-high roller mill; RMS, Model 924 or a hammermill; Bliss, model 22115) and 2 particle size variations (standard vs. blended). Increasing corn particle size variation was accomplished by blending 30% 400 μm corn, 40% 600 μm corn, and 30% 800 μm corn. Standard treatments were accomplished by grinding corn to an average of 600 μm with either mill. On d 75, pigs were transported to a commercial packing plant for processing and determination of carcass characteristics. The average analyzed complete diet mean particle sizes and standard deviations were 497, 540, 503, and 520 μm and 2.70, 2.75. 3.35, and 3.35 for the roller mill standard, roller mill blended, hammermill standard, and hammermill blended treatments, respectively. Diet flowability was calculated using angle of repose (AoR), percent compressibility, and critical orifice diameter (COD) measurements to determine the composite flow index (CFI). The AOR were 34.2, 33.0, 35.4, and 36.2º; COD were 32.0, 31.3, 30.0, and 33.0 mm; compressibilitys were 18.7, 18.4, 17.0, and 15.7%; and CFI were 52.9, 55.4, 53.9, and 53.2 for the roller mill standard, roller mill blended, hammermill standard, and hammermill blended treatments, respectively. There were no interactions or main effects of mill type on growth performance or carcass characteristics. However, pigs fed the blended diets had marginally significant decreased (P<0.083) average daily gain (ADG) compared to those fed the standard diets. No differences were observed in total feed cost or cost per lb of gain between treatments. Pigs fed blended diets also had marginally decreased (P<0.059) gain value and income over feed costs (IOFC) compared to those fed diets that were not blended. In conclusion, mill type used to grind corn and increasing particle size variation did not impact flowability metrics of complete diets. Mill type used to grind corn did not influence performance of finishing pigs, while increasing particle size variation by blending various particle sizes of corn led to a marginal reduction in ADG, gain value, and IOFC.
Keywords: Feed processing; finishing pigs; particle size